Re-thinking Herczegfalvy: the ECHR and the control of psychiatric treatment - Bartlett, Peter (Cambridge University Press, 2012)
This chapter forms part of a E Brems (ed.), Diversity and Human Rights: Rewriting Judgments of the ECHR (Cambridge: CUP, forthcoming 2013), in which lawyers and academics re-write judgments of the ECHR in a number of human rights areas.